Dynamic Strategies for Small Business - Seteroff, Sviatoslav Steve (Business Expert Press, 2012)
Formulation of a strategic plan for small business can be an envigorating experience for the small business owner. The potential for reducing costs, and time consuming practices, can be eliminated by implementing this innovative dynamic strategies model. The tools of analysis are straight forward and can be applied by any individual. This book will assist you in developing a viable strategic plan for your business that will be brief, clear, concise, and easily understood. The benefi ts of the dynamic strategies model may increase commitment to excellence, effectiveness of performance, and profi ts. An innovative approach to empowering the employees of an organization is presented. This dynamic approach assists in building a holistic organizational culture that fosters commitment across all levels of the organization. This book is a blend of traditional techniques with a new perspective of strategy. It is important to remember that it is people that make the difference, and we must never forget that although we manage things, we must lead people.